Deficiency of Mouse FHR-1 Homolog, FHR-E, Accelerates Sepsis, and Acute Kidney Injury Through Enhancing the LPS-Induced Alternative Complement Pathway - Li, Xiangru; Hao, Zhenhua; Liu, Xiaorong; Li, Wei (Frontiers in Immunology, 2020)
Alternative complement pathway (AP) plays an important role in the development of sepsis which is life threatening. Deficiency of factor H related protein 1 (FHR-1), which is a regulator of AP, has been considered as a susceptible factor for atypical hemolytic uremic syndrome (aHUS) and other types of nephropathy when an inducer such as infection exists. However, the underlying mechanism of the disease development is largely unknown. There is no report on CFHR1 gene knockout in any animal infection model and its function in vivo is still unclear. Here, a Cfhr1 knockout mouse was generated for investigating AP in sepsis and sepsis-induced acute kidney injury (AKI). We found that murine FHR-1 homolog (FHR-E) deficiency enhanced lipopolysaccharide (LPS)-induced AP activation both in vitro and in vivo, and that Cfhr1 knockout mice exhibited more severe sepsis and AKI in response to LPS challenge. These results indicated that FHR-E deficiency promoted LPS-induced sepsis and AKI through AP over-activation, providing a mouse model for studying AP regulation and sepsis. This study revealed the function of FHR-E in vivo, which may further provide hints to the pathogenesis of FHR-1 deficiency-related diseases by enhancing LPS-induced AP activation.